PENGARUH TOTAL ASSETS TURN OVER, DEBT TO EQUITY RATIO, PRICE EARNING RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Wayan Okti Anggriani; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Investors who are interested in investing in companies on the Indonesia Stock Exchange, of course, expect high returns. The development of the company's stock price greatly affects investors in investing. If the company's stock price increases, investors think that investing in shares will bring profit. This research was conducted with the aim of knowing the effect of total assets turn over, debt to equity ratio, price earning ratio on stock prices. The sample in this study is a transportation company listed on the Indonesia Stock Exchange from 2016 to 2018, using 15 sample companies selected using purposive sampling. Based on the research results, it shows that total assets turnover, debt to equity ratio, price earning ratio have a positive and significant effect on stock prices.